The Ultrasound-Assisted Synthesis of Effective Monodisperse Nickel Nanoparticles: Magnetic Characterization and Its Catalytic Activity in co2 Methanation - Casagrande-Denardin, J (Royal Society of Chemistry, 2016)
Homogeneous nickel nanoparticles were synthesized and supported over m-ZrO2 through a simple ultrasonic process. The microscopic and magnetic characterization of nanoparticles showed high quality and effective monodisperse size distribution. The catalytic performance of the samples, containing only 1% wt nickel, was evaluated for CO2 methanation reaction. The experimental results showed high activity (70%) and excellent selectivity to CH4 (90% at 720 K). This low-cost and simple fabrication method of a nanocatalyst proves to be a potential candidate for further application. © 2016 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.